2014
DOI: 10.1093/jac/dku305
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre cohort study on colonization and infection with ESBL-producing Enterobacteriaceae in high-risk patients with haematological malignancies

Abstract: Even though BSI with ESBL-E is still rare in this high-risk population, colonization rates are substantial and vary considerably between centres. In-hospital transmission of ESBL-E as assessed by molecular typing was the exception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 21 publications
6
68
1
1
Order By: Relevance
“…Several studies reported risk factors for cephalosporin-resistant, ESBL-pro or MDR bacteria in cancer and HSCT patients [10,12,13,16,22,29,32]. Onl handful describe risk factors for carbapenem-resistant infections in popula involving but not limited to transplant patients, mainly for K. pneumoniae.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported risk factors for cephalosporin-resistant, ESBL-pro or MDR bacteria in cancer and HSCT patients [10,12,13,16,22,29,32]. Onl handful describe risk factors for carbapenem-resistant infections in popula involving but not limited to transplant patients, mainly for K. pneumoniae.…”
Section: Outcomementioning
confidence: 99%
“…studies, mainly limited to single centers or countries, describe rates and ris for specific resistant pathogens, such as extended-spectrum β-lactamase (E producing Enterobacteriaceae or multidrug-resistant (MDR) bacteria in pat with cancer and HSCT recipients [10][11][12][13]. The majority, however, were perfo countries with high resistance rates in both the hospitalized and general populations [12][13][14].…”
mentioning
confidence: 99%
“…55 The association between colonization and subsequent infection has been reported for many MDR bacteria, such as VRE, ESBL-producing Enterobacteriaceae, P. aeruginosa, S. maltophilia and carbapenem or colistin resistant K. pneumoniae. 115,116 Therefore, decolonization before the onset of neutropenia seems appealing in case of carbapenem-resistant bacteria, but very few data on the efficacy of this approach exist in this setting. For this purpose, oral gentamycin or a combination of oral gentamycin and colistin were used, with eradication rate of 40-50%, which was higher than the spontaneous eradication rate, but tended to decrease after few weeks.…”
Section: Othersmentioning
confidence: 99%
“…[21][22][23][78][79][80][81][82][83][84][85][86][87][88][89][90] Most studies were conducted in the acute-care setting [21][22][23][79][80][81]83,85,87,[89][90][91] and identified a population of patients infected and/or colonized with MDR-E, either ESBL-E or CRE, or MDR-Enterobacteriaceae defined by resistance to multiple classes of drugs. Patients were assessed for persistence of colonization at study-specific intervals and variable durations of follow-up.…”
Section: Duration Of Colonizationmentioning
confidence: 99%
“…21,22 Studies also have described variability in detection of these bacteria from the gastrointestinal (GI) tract of the same individual over time (ie, positive culture followed by negative culture then reverting to positive). 21,23 Finally, certain extensively drug-resistant Enterobacteriaceae, particularly carbapenemase-producing bacteria, have no or limited treatment options, which makes the impact of even a single transmission event significant and provides the basis for a more conservative approach to duration of CP. …”
mentioning
confidence: 99%